2008
DOI: 10.1107/s1744309108026924
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary crystallographic studies of putative threonyl-tRNA synthetases fromAeropyrum pernixandSulfolobus tokodaii

Abstract: Threonyl-tRNA synthetase (ThrRS) plays an essential role in protein synthesis by catalyzing the aminoacylation of tRNA(Thr) and editing misacylation. ThrRS generally contains an N-terminal editing domain, a catalytic domain and an anticodon-binding domain. The sequences of the editing domain in ThrRSs from archaea differ from those in bacteria and eukaryotes. Furthermore, several creanarchaea including Aeropyrum pernix K1 and Sulfolobus tokodaii strain 7 contain two genes encoding either the catalytic or the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The sequence of ApThrRS-2 can be divided into three domains: the editing domain, an additional (unknown) domain of 109 residues, and the anticodon-binding domain. 8 The amino acid sequence in the editing domain of ApThrRS-2 is similar to that of PaThrRS with an identity of 37%. It has been reported that the two editing domains of PaThrRS form a dimer.…”
Section: Plausible Structure Of Apthrrs-2mentioning
confidence: 98%
See 4 more Smart Citations
“…The sequence of ApThrRS-2 can be divided into three domains: the editing domain, an additional (unknown) domain of 109 residues, and the anticodon-binding domain. 8 The amino acid sequence in the editing domain of ApThrRS-2 is similar to that of PaThrRS with an identity of 37%. It has been reported that the two editing domains of PaThrRS form a dimer.…”
Section: Plausible Structure Of Apthrrs-2mentioning
confidence: 98%
“…Therefore, it is apparent that the editing domains of EcThrRS are completely missing in ApThrRS-1, as predicted from sequence alignments. 8 The N-terminal and the Cterminal domains of ApThrRS-1 could be the catalytic and the anticodon-binding domains, respectively, and such possibilities will be further discussed with the detailed structures.…”
Section: Overall Structurementioning
confidence: 99%
See 3 more Smart Citations